Sesquiterpenolides from Inula racemosa and their Chemical Transformations - Kaur, Ramandeep; Chahal, K.K.; Bhardwaj, Urvashi (Asian Journal of Chemistry, 2016)
Inula racemosa roots are rich source of sesquiterpene lactones. Soxhlet extraction of roots using chloroform followed by column chromatography on silver nitrate impregnated silica gel led to the isolation of two sesquiterpene lactones namely alantolactone and isoalantolactone. These sesquiterpene lactones were subjected to chemical transformations using different reagents (Mg/methanol, CHBr3/KOH, LiAl[OC(CH3)3]3 and NaBH4) to afford modifications on their a-methylene-g-lactone moiety. The structures of isolated compounds and their transformation products were elucidated using spectroscopic techniques.